Kikuchi-Fujimoto disease in a young patient : a case report - Hairudin, Khairee Aqil; Wan Ramli, Wan Nurliyana; Ibrahim, Ismail; Saidin, Amira; Abd. Fuaat, Azliana; Zainulabid, Ummu Afeera (Persatuan Saintis Muslim Malaysia, 2022)
A rare form of lymphadenopathy called Kikuchi-Fujimoto disease (KFD), also known as histiocytic necrotizing lymphadenitis, was discovered in Japan in 1972 by Kikuchi and Fujimoto. It is characterised by persistent fever and localised cervical lymphadenopathy. This disease, typically known as histiocytic necrotising lymphadenitis, primarily affects young individuals. We reported a case of a young Malay female with prolonged fever and cervical lymphadenopathy. Her histopathological diagnosis was consistent with KFD. Nevertheless, she made a remarkable full recovery with a short course of corticosteroids. Therefore, Kikuchi disease must be considered in the differential diagnosis of cervical lymphadenopathy to minimise misdiagnoses and inappropriate therapies, given the rare prevalence.